At-Risk Youth and Attachment-Based Therapy: Implications for Clinical Practice - Bianco, Maria C. (Canadian Journal of Counselling and Psychotherapy, 2017)
Youth with a history of mental health concerns, trauma, aggression, and/or loss are vulnerable to high-risk behaviours and negative outcomes. Attachment-based therapy is investigated here to provide more effective suggestions for clinical practice. The following synthesis of strengths and limitations of current research reveal the need of at-risk youth to feel valued, connected, and supported. These needs originate from insecure or disorganized attachment patterns and subsequently lead to weak social understanding and interpersonal skills. Suggestions include development of caring relationships, interventions, emotional attunement between clients and therapists, expanded client self-understanding and acceptance, and increased awareness of attachment patterns and perceptions.